2019
DOI: 10.17051/ilkonline.2019.506900
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğretmenlerinin Sınıf İçi Ölçme ve Değerlendirmelerde Yazılı Yoklamalarda Kullandıkları Açık Uçlu Maddeleri Hazırlama Yeterlikleri

Abstract: Bu araştırmanın amacı ortaokul öğretmenlerinin sınıf içi ölçme ve değerlendirmeler kapsamında yazılı yoklamalarda kullandıkları açık uçlu maddeleri hazırlama yeterliklerini, açık uçlu madde yazımına yönelik kuramsal bilgileri ile kendi hazırladıkları maddeleri dikkate alarak değerlendirmektir. Araştırma, nicel araştırma yaklaşımı ile tarama modelinde yürütülmüştür. Araştırmanın örneklemini 167 öğretmen oluşturmuştur. Örnekleme yöntemi olarak maksimum çeşitlik örneklemesi kullanılmıştır. Veriler araştırmacılar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…sorusu akla gelmektedir. Bu konuda yapılan çalışmalar (Aydın ve Uçgun, 2020;Çintaş Yıldız, 2015;Göçer 2016;Güfta ve Zorbaz 2008;İnceçam, Demir ve Demir, 2018;Karatay ve Dilekçi, 2019) incelendiğinde bu araştırmaların da benzer sonuçlar verdiği, sınav evraklarında yer alan soruların çoğunlukla hatırlama ve anlama basamaklarını ölçtüğü sonucuna ulaşılmıştır.…”
Section: Introductionunclassified
“…sorusu akla gelmektedir. Bu konuda yapılan çalışmalar (Aydın ve Uçgun, 2020;Çintaş Yıldız, 2015;Göçer 2016;Güfta ve Zorbaz 2008;İnceçam, Demir ve Demir, 2018;Karatay ve Dilekçi, 2019) incelendiğinde bu araştırmaların da benzer sonuçlar verdiği, sınav evraklarında yer alan soruların çoğunlukla hatırlama ve anlama basamaklarını ölçtüğü sonucuna ulaşılmıştır.…”
Section: Introductionunclassified
“…Although open-ended questions are appropriate to measure high-level cognitive skills, there are some difficulties in scoring them (e.g., scoring not being objective, low content validity) (Atilgan, Kan & Dogan, 2009). In their study examining the appropriateness of open-ended questions used in tests prepared by middle school teachers, Incecam, Demir and Demir (2018) found that teachers made extensive use of open-ended questions. The results of a study by Sahin, Ozturk Boztunc and Teker Tasdelen (2015) reveal that open-ended questions were the fourth most preferred method of evaluation by pre-service teachers.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…e) The use of open-ended questions in measurement and evaluation (İnceçam et al, 2018;McMillan, 2017;MoNE, 2017;OECD, 2017;Silver, 1992).…”
Section: B)mentioning
confidence: 99%
“…As they are directly related to the purpose of this study, it is necessary to focus on the themes of measurement-evaluation and teacher-related studies. In terms of their use for measurement and evaluation, open-ended questions are characterized by the terms "constructed response items" and "extended response items" (Hogan & Murphy, 2007;İnceçam et al, 2018;McMillan, 2017). As Erhan Bingolbali & Hilmi Furkan Cevik,How Do Middle School Mathematics Teachers Conceptualize… [143] they allow students to create their answers, open-ended questions are frequently associated with written examinations among practitioners and are also closely associated with tasks such as essays allowing students to make statements about the posed issues (McMillan, 2017).…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation